2018
DOI: 10.3389/fimmu.2018.01358
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Lymphoma-Derived Extracellular Vesicles Change the Secretome of Fibroblasts Toward a CAF Phenotype

Abstract: Secretion of extracellular vesicles (EVs) is a ubiquitous mechanism of intercellular communication based on the exchange of effector molecules, such as growth factors, cytokines, and nucleic acids. Recent studies identified tumor-derived EVs as central players in tumor progression and the establishment of the tumor microenvironment (TME). However, studies on EVs from classical Hodgkin lymphoma (cHL) are limited. The growth of malignant Hodgkin and Reed–Sternberg (HRS) cells depends on the TME, which is activel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 41 publications
0
53
0
2
Order By: Relevance
“…Lymphoma cells play an important role in directing tumor immune escape by creating a feasible tumor microenvironment. A number of strategies are adopted by the cells to obtain this goal: (1) the direct recruitment of immune cells [67]; (2) the indirect “education” of normal cells to release a specific pattern of cytokines or chemokines [68,69,70]; and (3) the reprogramming of resident fibroblasts to cancer-associated fibroblasts (CAF) [71]. It is known that Treg cells exert immune-suppressive activity on lymphoma-infiltrating cytotoxic T cells, resulting in ineffective immune clearance [72].…”
Section: Ev-mediated Lymphoma Immune Escapementioning
confidence: 99%
See 1 more Smart Citation
“…Lymphoma cells play an important role in directing tumor immune escape by creating a feasible tumor microenvironment. A number of strategies are adopted by the cells to obtain this goal: (1) the direct recruitment of immune cells [67]; (2) the indirect “education” of normal cells to release a specific pattern of cytokines or chemokines [68,69,70]; and (3) the reprogramming of resident fibroblasts to cancer-associated fibroblasts (CAF) [71]. It is known that Treg cells exert immune-suppressive activity on lymphoma-infiltrating cytotoxic T cells, resulting in ineffective immune clearance [72].…”
Section: Ev-mediated Lymphoma Immune Escapementioning
confidence: 99%
“…LCEV-dependent cell-to-cell communication between distant lymphoma cells also involves educational mechanisms that are driven by CD30+ LCEVs. This mainly includes bidirectional cross-talk between malignant cells and resident fibroblasts [71]. Recent data have demonstrated that HL cells release LCEVs that express the full-length CD30 receptor and can locally modify the LME via interactions between their ligands (CD30L+) and neighboring cells.…”
Section: Ev-mediated Lymphoma Immune Escapementioning
confidence: 99%
“…HRS cells can educate fibroblasts to become CAFs. Dorsam et al [107] found that HL extracellular vesicles can change the secretome of fibroblasts toward a CAF phenotype. These vesicles were internalized by fibroblasts, which increased their migratory capacity, showed an inflammatory phenotype and increased expression of alpha-smooth muscle actin, a marker of CAFs.…”
Section: Education By Extracellular Vesiclesmentioning
confidence: 99%
“…These vesicles were internalized by fibroblasts, which increased their migratory capacity, showed an inflammatory phenotype and increased expression of alpha-smooth muscle actin, a marker of CAFs. Extracellular vesicle-treated fibroblasts enhanced the release of pro-inflammatory cytokines (e.g., IL-1α, IL-6, and TNF-α), growth factors (G-CSF and GM-CSF), and the pro-angiogenic factor VEGF [107] ( Figure 1). These findings were confirmed using a cHL xenograft model [107].…”
Section: Education By Extracellular Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation